Marangoni instabilities for convective mobile interfaces during drop exchange: Experimental study and CFD simulation - Javadi, A.; Karbaschi, M.; Bastani, D.; Ferri, J.K.; Kovalchuk, V.I.; Kovalchuk, N.M.; Javadi, K.; Miller, R. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2014)
[Display omitted] ► Experimental results indicate a significant delay in onset of Marangoni convection. ► The simulation results show an immediate Marangoni convection. ► Quasi-static isotherm equations cannot be simply applied for the mobile interfaces. The inflow pattern of liquid into a droplet is studied experimentally using a surface active dye and compared with results of CFD simulations. The results show visual agreement between experiments and simulations. The CFD simulations show also good agreement with the surface tension measured by drop profile analysis tensiometry (PAT). The inflow of the surfactant induces a Marangoni instability caused by the local arrival of the surfactant at the drop surface. The onset of this Marangoni instability observed experimentally has a delay of about 10s when compared with the simulation results. Different scenarios are discussed, including a boundary layer barrier, a kinetic-controlled adsorption mechanism, the way of renewing a mobile interface, and a critical Marangoni number required for the onset of such instability. It turns out that besides the commonly defined critical Marangoni number, the main reason for delay of Marangoni instability is possibly the mobility of the drop surface which can prevent the establishment of a quasi static adsorbed layer required for the appearance of such surface effect.